Ocular surface squamous neoplasia masquerading as pseudoepitheliomatous hyperplasia in chronic vernal keratoconjunctivitis - Ghosh Dastidar, Aditi; Khedia, Deepika; Goel, Sugandha (GMS Ophthalmology Cases, 2024)
We report a rare case of ocular surface squamous neoplasia (OSSN) masquerading as pseudoepitheliomatous hyperplasia in chronic vernal keratoconjunctivitis (VKC). A 24-year-old man presented with a history of bilateral VKC since childhood with a superior limbal mass in the right eye. There was a history of use of intermittent corticosteroids in the past. He underwent impression cytology followed by excision biopsy with wide margins (no touch technique), cryotherapy and amniotic membrane transplantation. Histopathological analysis confirmed the diagnosis of OSSN with mild to moderate dysplasia. This case highlights the importance of strong clinical suspicion and detailed cytological and histopathological examination for early detection and management of OSSN.